Central apnoea associated with subcortical haemorrhage in the left temporal lobe. Issue 3 (25th February 2010) - Nezu, Tomohisa; Naganuma, Masaki; Shono, Yuji; Toyoda, Kazunori; Minematsu, Kazuo
Abstract : Temporal-lobe lesions sometimes cause apnoeic attacks in infants, but they rarely cause apnoeic attacks in adults. An 80-year-old woman with a history of hypertension was admitted to hospital because of global aphasia and mild right hemiparesis. The admission head CT showed small subcortical haemorrhage in the left temporal lobe. Immediately after the CT, her respiratory rate decreased to 3/min, and her arterial blood gas analysis showed respiratory acidaemia without any evidence of airway obstruction or additional neurological deficits. Thus, she required artificial ventilation. Single-photon emission CT performed on the same day showed hyperperfusion in the left temporal region, but the electroencephalogram showed no epileptic spike. When mechanical ventilation was discontinued on the fourth hospital day, she was alert, and her respiratory rhythm was normal. This is the first report of a central apnoeic attack associated with intracerebral haemorrhage in the left temporal lobe in an adult patient. It is important to note that a small haematoma in the temporal lobe can trigger life-threatening apnoea, probably by cortical stimulation.